English Competence of Generation Z: A Study at IAIN Kudus - Azizah Maulina Erzad; Lusi Ardanisa Mei Clarita; Yunita Salma (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2019)
Abstract. Industrial revolution 4.0 era which is also called as disruptive era gives many benefits for several aspects especially in education. It becomes easier for the teacher to use any kinds of media for teaching English and for the students to find English materials by themselves. The recent students of English Education Department IAIN Kudus belong to generation Z students. As generation Z students who live in 4.0 era, they are able to access many kinds of information or knowledge and improve their English competences from any resources easily. This paper aims to identify the way of the generation Z learn English, the difficulties encountered by them in learning English, and the solutions or suggestions to overcome the difficulties. This study employed mixed methods research. In conducting this research, the researchers used observation, open-ended questionnaire and documentation to collect the data. The participants were 39 students of English Education Department at IAIN Kudus. The results showed that 60% students use gadgets to study English, 15% use books, and 25% use both of them. Meanwhile, 50% students have difficulties in speaking, 10% in listening, 6% in reading, 17% in writing, and 17% in those four competences. Some solutions or suggestions were revealed to resolve the difficulties. The solutions were extended for each language competence.Keywords: English Competence, Generation Z, IAIN KudusAbstrak. Era revolusi industri 4.0, yang juga dikenal dengan era disruptif, memberikan banyak keuntungan dalam berbagai aspek khususnya dalam pendidikan. Hal ini akan memudahkan guru untuk menggunakan berbagai jenis media untuk mengajar Bahasa Inggris dan juga bagi mahasiswa untuk mencari materi Bahasa Inggris sendiri. Mahasiswa jurusan Bahasa Inggris IAIN Kudus juga termasuk mahasiswa generasi Z. Sebagai mahasiswa generasi Z yang tinggal di era 4.0, mereka mampu mengakses berbagai macam informasi atau pengetahuan untuk memperbaiki kompetensi mereka dari berbagai sumber dengan mudah. Paper ini bertujuan untuk mengidentifikasi cara bagaimana generasi Z belajar Bahasa Inggris, kesulitan-kesulitan yang dihadapi mereka, dan solusi atau saran untuk menghadapi kesulitan tersebut. Penelitian ini menggunakan metode campuran (mixed methods), dan dalam mengumpulkan data penulis menggunakan teknik observasi, kuesioner, dan dokumentasi. Peserta penelitian ini adalah 39 mahasiswa jurusan Bahasa Inggris IAIN Kudus. Hasil menunjukkan bahwa cara mereka belajar 60 % menggunakan gawai, 15 % menggunakan buku, dan 25 % menggunakan dua-duanya. 50 % mahasiswa mengalami kesulitan dalam berbicara Bahasa Inggris, 10 % mendengarkan, 6 % dalam membaca, 17 % dalam menulis, dan 17 % mengalami kesulitan dalam keempat-empatnya. Beberapa solusi ditawarkan untuk menghadapi masalah tersebut, terutama di masing-masing keahlian berbahasa.Kata kunci: kompetensi bahasa Inggris, generasi Z, IAIN Kudus